2013
DOI: 10.1007/s00198-013-2546-8
|View full text |Cite
|
Sign up to set email alerts
|

Atypical femoral fractures: retrospective radiological study of 319 femoral fractures and presentation of clinical cases

Abstract: The most recent literature reports that the incidence of atypical fractures is 0.6 %. However, taking into consideration only the fracture locations suitable for the identification of atypical fractures, the percentage rises to 5 %. To date, there is still no clarity on the exact etiology of fractures even if it seems to be related to a bone mineral component alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 13 publications
0
21
0
2
Order By: Relevance
“…The estimated incidence in patients given oral BPs at doses used for osteoporosis is lower at less than 1 in 100,000 patient treatment years [18]. In contrast, the incidence of AFF is not established [21]. A dose-response relationship has not been documented but the risk appears related to duration of treatment.…”
Section: Introductionmentioning
confidence: 97%
“…The estimated incidence in patients given oral BPs at doses used for osteoporosis is lower at less than 1 in 100,000 patient treatment years [18]. In contrast, the incidence of AFF is not established [21]. A dose-response relationship has not been documented but the risk appears related to duration of treatment.…”
Section: Introductionmentioning
confidence: 97%
“…Lenart et al (2) described as "atypical" fractures that involved the strongest part of the femur, the subtrochanteric and diaphyseal region, and then the American Society for Bone and Mineral Research Task force (3) identified major and minor features that define distinctly "typical" osteoporotic femoral fractures from "atypical" fractures. A recent review demonstrated that the incidence of atypical femoral fractures (AFFs) is 0.6%, according to data from the most recent literature, referred to all femoral fractures, including both medial fractures, lateral and diaphyseal fractures (4). Moreover, in the literature are reported atypical fractures that occur to other skeletal districts in addition to femur (1) and several case reports in the literature related periprosthetic femoral fractures to the same or similar pathology as that of an atypical femoral fracture (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies have suggested that bisphosphonates may prevent or may be used to treat aseptic loosening (23), or to prevent the decrease in proximal femoral BMD usually seen after hip replacement (24,25). Patients with THA and risk factors for loosening should be screened for osteoporosis and have regular radiological surveillance (3), especially if treated with BF for monitoring of any atypical periprosthesis fractures, in particular in areas neighboring the end of the prosthesis stem (26,27). Bone quality of the hip joint has become an important risk factor limiting the durability of THA (28).…”
Section: Discussionmentioning
confidence: 99%